P1-S1.50 A decade of early syphilis in East and inner city London. (10th July 2011) - Anderson, H; Williams, A; Zirngibl, M; Fatima, J; Symonds, M; Goh, B
Abstract : Background: Following a rise in cases of early syphilis in the UK, a programme of national enhanced surveillance (ES) was commenced in 2001 by the Health Protection Agency with the aims of establishing case distribution and trends in behaviour groups. Local analysis of data acquired via the ES has led to changes to our services in targeting specific high risk groups through increased outreach and community based screening and improvement in health promotion interventions. These include screening for syphilis in all patients attending STI/HIV clinics, dedicated MSM and CSW clinics and outreach work to gay saunas and CSW. The purpose of this study is to look at the epidemiology of infectious syphilis in East and Inner City London over the past decade to provide data on the burden of infection and to further inform local strategy as a measure of outbreak control. Methods: Data were obtained from patients with infectious syphilis attending the Royal London and St Bartholomew's Hospitals in the City and East London from 2001 to 2010. The data were collated and analysed from the ES form. Results: Of 778 patients, 39% had primary syphilis, 37% secondary syphilis and 24% had early latent syphilis; 94% were male, 6% female, 51% white British and 12% were Afro-Caribbean. Of the male, 85% were MSM. Three cases were age <16, 27% 17–30 years and 34% were >40 years of age. 257 (32%) were HIV positive. The main reasons for attendance at clinic were for routine screen (24%), symptom management (46%), consequent of partner notification (6%). 18% had one partner, 58 % had 2–9 partners, 19% had 10–99 partner, and 2% had ≥100 partners past 3 months. 82% acquired their syphilis in London, 4% acquired elsewhere in UK, and 8% in Europe. 4% were female sex workers and 6% acquired their infection through sex workers. 10% acquired their infection in gay saunas, 21% acquired through clubs and 14% via the internet. There were 21 cases in 2001, 115 in 2006 and 44 cases in 2010. Conclusions: (1) The syphilis outbreak peaked in 2006 and has decreased by 62% in 2010 indicating that intervention strategy which is still in place, is having an effect. (2) More preventive work need to be done in clubs and on internet dating. (3) HIV coinfection is common and is a cause for concern as syphilitic ulcers enhanced transmission of HIV and HIV coinfection can lead to more severe syphilis manifestation. (4) 21% had 10 partners past 3 months, mainly untraceable, and sex abroad will continue to fuel the outbreak.